2014
DOI: 10.4097/kjae.2014.66.2.105
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study among normal saline, water soluble gel and 2% lidocaine gel as a SLIPA lubricant

Abstract: BackgroundThis study was designed to find appropriate lubricant for streamed lined liner of pharyngeal airway™ (SLIPA™). We evaluated the incidence of sore throat, nausea, vomiting, hoarseness, paresthesia and blood stain after using saline, water soluble gel and 2% lidocaine gel as a SLIPA™ lublicant.MethodsOne hundred twenty three patients scheduled for minor surgery to whom the SLIPA™ was considered suitable were randomly allocated to one of three groups which receive normal saline, water soluble gel or 2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Yet contrary to our hypothesis, the initial intubation success rate was similar with the two devices. One possibility is that in fact, the trachea is relatively easy to intubate in patients with cervical immobilisation; direct laryngoscope success rates are as high as 80% . Also, our study participants were probably very experienced with the lightwand: one study reported a success rate as high as 96% in patients with a semi‐hard cervical collar .…”
Section: Discussionmentioning
confidence: 92%
“…Yet contrary to our hypothesis, the initial intubation success rate was similar with the two devices. One possibility is that in fact, the trachea is relatively easy to intubate in patients with cervical immobilisation; direct laryngoscope success rates are as high as 80% . Also, our study participants were probably very experienced with the lightwand: one study reported a success rate as high as 96% in patients with a semi‐hard cervical collar .…”
Section: Discussionmentioning
confidence: 92%